Students Creative Thinking Ability with Reflective Cognitive Style on The Phytagoras Theorem - Kasyifatun Naza; Syamsuri Syamsuri (Journal of Education and Learning Mathematics Research (JELMaR), 2022)
Mathematics is a universal science that cannot be separated from human life. Mathematics has an important role in supporting the development of science and technology. In learning mathematics, students' creativity is needed because in mathematics students are expected to be able to come up with new creative ideas in analyzing and solving problems. The way students solve problems will be different according to their cognitive style. So that differences in cognitive styles can trigger differences in students' creative thinking. The type of research used in this research is qualitative research with descriptive method. The subjects in this study were students of class VIII K at SMP Negeri 2 Balaraja who had received the Pythagorean theorem material. Subject selection was done by purposive sampling technique. The instruments used in this study were test and non-test instruments. The test instrument used is the Matching Familiar Figures Test (MFFT) test sheet and the creative thinking ability. While the non-test instrument used in this study was an interview guide. The data analysis of this research used the constant comparative method. Data analysis in this study was carried out through three stages, namely: 1) data reduction, (2) data presentation, (3) drawing conclusions.Based on the results of the data analysis and discussion that has been presented, it can be concluded that based on the reflective cognitive style, students' mathematical creative thinking abilities can be grouped into 2 groups in each indicator with different creative thinking abilities.